2015
DOI: 10.1007/s00535-015-1088-6
|View full text |Cite
|
Sign up to set email alerts
|

Achalasia symptom response after Heller myotomy segregated by high-resolution manometry subtypes

Abstract: Background Achalasia is classified into three HRM subtypes that predict outcomes from diverse management strategies. We assessed if symptomatic response varied when a single management strategy—Heller myotomy (HM)—is employed. Methods Treatment-naive subjects with achalasia referred for HM were followed in this observational cohort study. Chicago criteria designated achalasia subtypes (subtype I: no esophageal pressurization; subtype II: panesophageal pressurization in ≥20 % swallows; subtype III: premature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
(37 reference statements)
0
22
0
1
Order By: Relevance
“…Residual symptoms are reportedly highest with type 3, where HM is favored over PD. The common theme across all three subtypes is adequate LES disruption; indeed, use of a uniform surgical approach with HM demonstrated no differences in outcome across the three subtypes . Nevertheless, PD remains an easy and clinically useful approach to achalasia management, best utilized in older patients, females and particularly subtype 2 .…”
Section: Perspectives On Managementmentioning
confidence: 96%
“…Residual symptoms are reportedly highest with type 3, where HM is favored over PD. The common theme across all three subtypes is adequate LES disruption; indeed, use of a uniform surgical approach with HM demonstrated no differences in outcome across the three subtypes . Nevertheless, PD remains an easy and clinically useful approach to achalasia management, best utilized in older patients, females and particularly subtype 2 .…”
Section: Perspectives On Managementmentioning
confidence: 96%
“…In this study, we identified dominant symptoms using questionnaire designation. Similarly, global esophageal symptoms over the previous two weeks were characterized on VAS using GSS 14, 17 . The dominant symptom identification and GSS allowed assessment of both dominant and global symptoms, and facilitated follow-up of esophageal symptoms over time in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, physicians have sought to identify prognostic factors that can be used to select the most appropriate therapy for specific individuals. Thus far, elder age, male sex and postoperative LES >10 mmHg have been reported to be related to a favorable prognosis . Since the application of HRM and the Chicago classification, different manometric subtypes have also been proposed to serve as potential prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…reported that elder age was the only independent factor that was associated with the success rate of PBD (85.7% in patients <40 years vs 38.5% in those >40 years). Some studies have demonstrated that HRM subtypes of achalasia may be important predictors of patient's clinical outcomes . However, it remains controversial whether symptomatic outcomes after treatment are similar across achalasia subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation